2021
DOI: 10.1186/s12916-021-01957-y
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone induces an imbalanced fetal-placental-maternal bile acid circulation: involvement of placental transporters

Abstract: Background The use of prenatal dexamethasone remains controversial. Our recent studies found that prenatal dexamethasone exposure can induce maternal intrahepatic cholestasis and have a lasting adverse influence on bile acid (BA) metabolism in the offspring. The purpose of this study was to investigate the effects of dexamethasone on fetal-placental-maternal BA circulation during the intrauterine period, as well as its placental mechanism. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…Unlike the most regular course of dexamethasone during pregnancy (single course), a longer intervention (multiple courses) with dexamethasone was used in the PDE rat experiments to better reveal the potential developmental toxicity of dexamethasone exposure during pregnancy. Nevertheless, the PDE rat results of this study may still provide valuable insights for clinical research and practice, as the animal results of this study and some previous studies 14 , 67 , 68 , 69 are relatively consistent with clinical findings. In addition, how the abnormal gut microbiota mediates the occurrence of cholestatic liver injury through influencing intestinal bile acid conversion and how to intervene effectively are worthy of further study.…”
Section: Discussionsupporting
confidence: 75%
“…Unlike the most regular course of dexamethasone during pregnancy (single course), a longer intervention (multiple courses) with dexamethasone was used in the PDE rat experiments to better reveal the potential developmental toxicity of dexamethasone exposure during pregnancy. Nevertheless, the PDE rat results of this study may still provide valuable insights for clinical research and practice, as the animal results of this study and some previous studies 14 , 67 , 68 , 69 are relatively consistent with clinical findings. In addition, how the abnormal gut microbiota mediates the occurrence of cholestatic liver injury through influencing intestinal bile acid conversion and how to intervene effectively are worthy of further study.…”
Section: Discussionsupporting
confidence: 75%
“…For example, serum bile acid levels were elevated in prenatal dexamethasone-treated male fetuses but not in female fetuses. Elevated total serum bile acid in male fetal rats and decreased in female fetal rats were observed in PDE rat model, which was attributed to the dysfunction of placental bile acid transporters [ 64 ]. Recent studies have identified sex-dependent epigenetic mechanisms involved in sex differences in adrenal developmental toxicity induced by PDE, i.e., intrauterine dexamethasone leads to sex differences in histone acetylation and expression levels of 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) by decreasing GR binding to the androgen receptor (AR) in male offspring or increasing GR binding to ERβ in female offspring, the latter mediating sex differences in adrenal developmental toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In a breast cancer cell line overexpressing BCRP, dexamethasone significantly decreased BCRP activity, thus increasing the entrance of mitoxantrone into the cell and its cytotoxicity [46]. Two further studies confirmed the impact of dexamethasone on the modulation of the placental barrier in pregnant women and revealed that it not only involved P-gp but also other transporters, such as modulation of BCRP transcription and activity and the increase of MRP4 expression, which may affect drug toxicity and efficacy during pregnancy [47,48].…”
Section: Effect Of Dexamethasone On Other Transporters and Metabolism...mentioning
confidence: 92%